Impact of pneumococcal conjugate vaccine (PCV7 and PCV13) on pneumococcal invasive diseases in Italian children and insight into evolution of pneumococcal population structure. Issue 35 (16th August 2017) - Camilli, Romina; D'Ambrosio, Fabio; Del Grosso, Maria; de Araujo, Fernanda Pimentel; Caporali, Maria Grazia; Del Manso, Martina; Gherardi, Giovanni; D'Ancona, Fortunato; Pantosti, Annalisa; ,
Abstract: Background: The use of PCV7 for children immunization was gradually implemented in the Italian regions starting from 2006 and was replaced by PCV13 in 2010–2011. In this study we aimed to assess the PCV impact on invasive pneumococcal diseases (IPD) incidence, serotype distribution and antibiotic resistance in Italian children under 5 years old. Methods: All IPD cases in children from 5 Italian regions (Emilia-Romagna, Lombardia, A. P. Bolzano, A. P. Trento, and Piemonte) reported through the nationwide surveillance system during 2008–2014 were included in this study. Pneumococcal isolates were subjected to serotyping, antibiotic susceptibility testing, and clonal analysis according to standard methods. Results: During the study period overall IPD incidence decreased from 7.8 cases/100, 000 inhabitants in 2008 to 3.0 cases/100, 000 in 2014 (61% decrease, P < 0.001). In particular, from 2008 to 2014, PCV7-type IPD decreased from 2.92 to 0.13 cases/100, 000 inhabitants (95% decrease, P < 0.001) while PCV13-non-PCV7 type IPD decreased from 3.2 to 0.89 cases/100, 000 inhabitants (72% decrease, P = 0.008). Conversely, non-vaccine serotype (NVS) IPD increased overtime, becoming more common than PCV13 serotype IPD in 2013–2014. Emergent NVS 24F and 12F were the most prevalent in 2014. Antibiotic resistance testing revealed an overall increasing trend in penicillin resistance, from 14% in 2008 to 23% in 2014. Erythromycin resistance showed a downward trend, from 38% in 2008 to 27% in 2014. While in 2008 PCV13 serotypes were the major responsible for antibiotic resistance, during the following years antimicrobial resistance due to NVS increased, mainly as a result of expansion of pre-existing clones. Conclusions: Both PCVs led to a substantial decrease in vaccine-related IPD incidence in the children population. However NVS-related IPD increased, becoming the most prevalent in the last two-years period. Continuous surveillance is an essential tool to monitor evolution of pneumococcal population causing IPD in children.